2022
DOI: 10.1021/acs.joc.2c01495
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylation of Propargyl Alcohols with Sulfinamides for the Synthesis of Allenyl Sulfones

Abstract: A regio-and chemoselective sulfonylation of propargyl alcohols with sulfinamides in 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) was developed. It provided straightforward and mild access to multi-substituted allenyl sulfones by using sulfinamides as the sulfonyl sources. This transformation was promoted by HFIP and did not require any catalysts or oxidants, which allowed for the successful conversion of various tertiary and secondary propargyl alcohols into allenyl sulfones in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Interestingly, a higher yield of 93 % was obtained by increasing the reaction temperature to 80 °C after 1.0 h. However, when the reaction was performed at room temperature, the yield greatly decreased with mostly starting material. Moreover, increasing or decreasing the amount of sodium sulfinate 2 a did not give a better yield (entries [13][14]. Further screening of the amount of acid promoter confirmed that 1.5 equiv.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, a higher yield of 93 % was obtained by increasing the reaction temperature to 80 °C after 1.0 h. However, when the reaction was performed at room temperature, the yield greatly decreased with mostly starting material. Moreover, increasing or decreasing the amount of sodium sulfinate 2 a did not give a better yield (entries [13][14]. Further screening of the amount of acid promoter confirmed that 1.5 equiv.…”
Section: Resultsmentioning
confidence: 96%
“…To the best of our knowledge, this is the first example of allenyl sulfones obtained by the reaction of propargylic alcohols with readily available sodium sulfinate as a sulfonyl source. At the same time when this manuscript was prepared, Li's group reported a practical approach to construct alleneyl sulfones by the sulfonylation of propargylic alcohols with sulfinamides as a sulfonyl source under mild conditions [14] . Compared with Li's work, our method uses cheap and readily available sodium sulfinate as a sulfonyl source, whereas the corresponding product yield is relatively higher.…”
Section: Introductionmentioning
confidence: 97%
“…In 2022, sulfonylation of secondary and tertiary propargylic alcohols 1 with sulfonamides 182 access to allenyl sulfones 183 can promote by HFIP solvent (Scheme 79). [73] In the combination process, the OH group of propargylic alcohol was activated by HFIP. An allenyl carbocation A' formed uring tautomerization with A. S-Substitution of A' by sulfonyl nucleophile gave allenyl sulfoximine B, which hydrolyzed to produce allenyl sulfone 183.…”
Section: Reaction With S Nucleophilesmentioning
confidence: 99%
“…[4] Sulfinyl amides are commercially available, stable and easyto-handle building blocks for organic synthesis, which have been widely used as ideal N-nucleophiles. We previously reported a sulfonation of allylic alcohols [5] and propargyl alcohols [6] by using sulfinyl amides as sulfur nucleophiles (Scheme 1A). In order to explore the use of sulfinyl amide for other purposes than sulfonation reagent, we speculated that it may also be used as thiolation reagent for the thiolation of indoles.…”
Section: Introductionmentioning
confidence: 99%